Velocidad de infiltración de agua en el subsuelo de las parroquias Veracruz y madre tierra, cantones Pastaza y Mera, provincia de Pastaza. - Lema Ruiz, Cinthya Monserrath (2016)
The infiltration rate is the movement that the water takes from the surface into the soil at atmospheric pressure in function of the time , this natural phenomenon depends mainly on the amount of water available to infiltrate , soil type , surface condition and saturation level. This research work is aimed to determine the infiltration rates presented in the types of soil in the communities La Esperanza and Playas de Pastaza of Veracruz and Madre Tierra parishes respectively, Pastaza canton, Pastaza province; related to its grain size and texture, using the AASHTO method for its classification. With the purpose of knowing the infiltration rate in each of the pits analyzed, the double ring infiltrometer method was used and, to determine the classification of the soils of each sample obtained, granulometry tests and Atterberg limits were made. A total of 40 samples taken from the two communities under study were analyzed, determining the existence of 5 soil types, which are: A-2-4 ( gravels and silty clayey sand ) in a 20.51% of the total the investigated samples , A-2-5 ( gravels and silty clayey sand ) in a 58.97 % , A-2-7 ( gravels and silty clayey sand ) in a 10.26 % , A-5 ( loamy soils ) in a 5.13 % and finally A-7-5 ( clay soils ) at 5.13% . In addition, through this research has established the typical infiltration speed ranges of each type of soil: A-2-4 ( gravels and silty clayey sand ) shows a range from 10 mm/h to 20 mm/h , A-2-5 ( gravels and silty clayey sand ) ranges from 4 mm/h to 20 mm/h , A-2-7 ( gravels and silty clayey sand ) ranges from 5 mm/h to 6 mm/h, A-5 ( loamy soils ) ranges that are between 3 mm/h to 4 mm/h and finally A-7-5 ( clay soils ) with speeds from 3 mm/h to 5 mm/h.